Uncovering Price Memory in Indian Oil and Gas Stocks: A Rescaled Range Approach - Sakshi Singh, Disha Singh; Shalini Raj (Journal of Informatics Education and Research, 2025)
This study examines the behaviour of the Indian capital market with a particular focus on the Oil and Gas sector, aiming to evaluate the validity of weak-form market efficiency. The analysis centers on the NIFTY Oil & Gas Index and its five leading constituent companies. Employing an empirical methodology, the study utilizes secondary time-series data and applies statistical techniques such as the Unit Root Test, Runs Test, and the Hurst Exponent through Rescaled Range Analysis. These methods are used to assess stationarity, randomness, and the presence of long-term memory in stock price movements. The findings suggest that stock prices do not conform entirely to the assumptions of weak-form efficiency, indicating the potential for historical price data to inform future market predictions. Moreover, the identification of long memory effects implies persistent trends within the price series. These outcomes offer practical implications for investors, financial analysts, and institutional decision-makers in formulating strategic investment and risk management approaches.